APEC at 20 recall, reflect, remake - Kesavapany, K.; Lim, Hank (Institute of Southeast Asian Studies, 2009)
Spanning 20 years of history, the achievements of APEC may seem uneventful in the eyes of some observers. Yet careful deliberation will point to APEC's many remarkable high points as well as some of the challenges. The foundations of APEC were set in place about 40 years ago based on the achievements of the Association of Southeast Asian Nations (ASEAN) and the Pacific Economic Cooperation Council (PECC). One of the cornerstones of APEC's vision is to achieve a free and open trade area among its member economies. This vision is anchored in the Bogor Goals that remain the centrepiece of the APEC process. The Bogor Goals represent a cause for celebration as well as angst. Celebration because the region has moved towards achieving a much more liberalized environment of trading and investment since 1989, angst because the deadlines for achieving the goals have not yet been fully realized. Today, APEC embraces many of the world's dynamic developed and developing economies that are better poised to meet the new challenges of this century. For those seeking to get a quick sweep of APEC, this book recalls, reflects and provides enough food for thought on the possible remake of APEC. The chapters are carefully written by experts who have been directly involved in the APEC process one way or another. The invaluable insights serve to place the whole APEC process in a balanced perspective, yet with candid deliberations.